ANALYSIS OF THE EFFECT OF REGIONAL MINIMUM WAGES AND ECONOMIC GROWTH ON JOB OPPORTUNITIES IN CENTRAL KALIMANTAN - Harati, Rima (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to determine the effect of the minimum wage variable and economic growth on employment opportunities partially or simultaneously in Central Kalimantan. This research was carried out in Central Kalimantan by taking the research time span between 2011-2022. The analytical method used is multiple regression analysis and the results of the analysis show that the Regional Minimum Wage partially has a significant effect on employment opportunities in Central Kalimantan. Partial economic growth has no significant effect on employment opportunities in Central Kalimantan. The Regional Minimum Wage simultaneously has a significant effect on employment opportunities in Central Kalimantan. Simultaneous economic growth has no significant effect on employment opportunities in Central Kalimantan.